Factors associated with medication information in diabetes care: differences in perceptions between patients and health care professionals - Längst, Gerda (Patient Prefer Adherence, 2015)
PURPOSE: This qualitative study in patients with type 2 diabetes and health care professionals (HCPs) aimed to investigate which factors they perceive to enhance or impede medication information provision in primary care. Similarities and differences in perspectives were explored. METHODS: Eight semistructured focus groups were conducted, four with type 2 diabetes patients (n=25) and four with both general practitioners (n=13) and health care assistants (n=10). Sessions were audio and video recorded, transcribed verbatim, and subjected to computer-aided qualitative content analysis. RESULTS: Diabetes patients and HCPs broadly highlighted similar factors as enablers for satisfactory medication information delivery. Perceptions substantially differed regarding impeding factors. Both patients and HCPs perceived it to be essential to deliver tailored information, to have a trustful and continuous patient–provider relationship, to regularly reconcile medications, and to provide tools for medication management. However, substantial differences in perceptions related to impeding factors included the causes of inadequate information, the detail required for risk-related information, and barriers to medication reconciliation. Medication self-management was a prevalent topic among patients, whereas HCPs’ focus was on fulfilling therapy and medication management responsibilities. CONCLUSION: The findings suggest a noteworthy gap in perceptions between information provision and patients’ needs regarding medication-related communication. Medication safety and adherence may be improved if HCPs collaborate more closely with diabetes patients in managing their medication, in particular by incorporating the patients’ perspective. Health care systems need to be structured in a way that supports this process.